Isolation, characterization and the functional properties of cellulosic arabinoxylan fiber isolated from agricultural processing by-products, agricultural residues and energy crops - Yadav, Madhav P.; Kale, Madhuvanti S.; Hicks, Kevin B.; Hanah, Kyle (Food hydrocolloids, 2017)
Water insoluble cellulosic arabinoxylan fibers were prepared from low-valued agricultural processing by-products, agricultural residues and energy crops by removing the alkali-extractable hemicelluloses and processing the alkali insoluble material under high temperature and high shear conditions. The yield of these fibrous plant materials varied from 14.3 to 59.90% and most of them contained more than 90% insoluble dietary fiber. Sugar composition and glycosyl-linkage analysis show that they are composed of cellulose and arabinoxylans indicating that they have a typical cellulosic arabinoxylan structure. They have very high water holding capacity varying from 6.374 to 74.33 g/g (water/fiber), indicating their usefulness in many food system applications as moisture management aids and texturizing agents. Their ORAC values vary from 352 to 1560 μmole Trolox/100 g showing that they have the ability to provide antioxidant activity in foods, as well as offering other functionality and health-promoting benefits of dietary fiber. [Display omitted] •Isolation of water insoluble fibers from agricultural processing by-products.•These fibers are hydrocolloids with high water holding capacity.•They can be useful ingredients in many food products.•They have ability to provide health-promoting benefits of dietary fiber.